2021
DOI: 10.1002/cbdv.202001010
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Characterization of a Novel Water‐Soluble Polysaccharide from Edible Mushroom Leucopaxillus giganteus and Its Antitumor Activity on H22 Tumor‐Bearing Mice

Abstract: In the present study, a novel cold water‐soluble polysaccharide fraction (LGP) with the average molecular weight of 1.78×106 Da was extracted and purified from Leucopaxillus giganteus and its primary structure as well as in vivo antitumor activity was evaluated. The monosaccharide composition of LGP was determined by ion chromatography to be galactose, xylose, glucose and fucose in a molar ratio of 2.568 : 1.209 : 1 : 0.853. Its backbone was composed of α‐D‐Glu, α‐D‐Xyl, α‐D‐Gal and α‐L‐Fuc. The results of in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The absorption peaks at 902.45 cm −1 and 812.03 cm −1 were attributed to the α ‐ and β ‐type glycosidic bond, respectively [25] . In addition, no absorption peak was found at about 1730 cm −1 , indicating that they do not contain uronic acid, which is consistent with the results of chemical composition [26] …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The absorption peaks at 902.45 cm −1 and 812.03 cm −1 were attributed to the α ‐ and β ‐type glycosidic bond, respectively [25] . In addition, no absorption peak was found at about 1730 cm −1 , indicating that they do not contain uronic acid, which is consistent with the results of chemical composition [26] …”
Section: Resultssupporting
confidence: 85%
“…[25] In addition, no absorption peak was found at about 1730 cm À 1 , indicating that they do not contain uronic acid, which is consistent with the results of chemical composition. [26]…”
Section: Characterization Of Polysaccharides Fourier Transform Infrar...mentioning
confidence: 99%
“…The ampoules were sealed under nitrogen purge, and the samples were hydrolyzed at 120 • C for 3 h. The acid hydrolysis solution was transferred to a glass tube through aspiration, and 10 mL of deionized water was added before mixing; then, 100 µL of the solution was aspirated, and 900 µL of deionized water was added. The supernatant was centrifuged at 12,000× g for 5 min, and the monosaccharide composition of PFSP-2-1 was determined using an ion chromatograph equipped with a Dionex Carbopac TMPA20 (3 × 150) column [45].…”
Section: Monosaccharide Composition Analysismentioning
confidence: 99%
“…In addition to autophagy, tumor cell proliferation can be inhibited by a variety of mechanisms, including cell cycle arrest, cell apoptosis, secondary necrosis, and stimulation of macrophages [ 159 ]. Niu et al [ 160 ] isolated a novel cold water-soluble polysaccharide fraction (LGP) from Leucopaxillus giganteus and found that LGP could effectively protect the thymus and spleen immune organs and inhibit the proliferation of the hepatoma H22 solid tumor in a dose-dependent manner. Further studies indicated that the antitumor mechanism of LGP may be the induced apoptosis of H22 cells through S-phase arrest and the mitochondria-mediated apoptosis pathway.…”
Section: In Vivo Bioactivity Of Tfpsmentioning
confidence: 99%